O uso de “matemágicas” no processo de ensino-aprendizagem - Santana, Paulo Sérgio Fontes (2024)
This dissertation presents a collection of “mathemagics” that can be used in the classroom, exploring their potential contributions to the teaching process-learning. The difference of this work is that, in addition to providing step-by-step each “mathemagic” also presents the formalized mathematical explanation of each one. It also includes an analysis of the application of 3 of these “mathemagics” in a class of high school, bringing the students’ perception to them. The target audience of this work are basic education Mathematics teachers, as it aims to encourage the use of mathematical tricks as an ally in teaching